THE INFLUENCE OF DISCIPLINE AND WORK MOTIVATION ON TEACHER PERFORMANCE AT DEVELOPMENT PRIVATE HIGH SCHOOL TANAH JAVA DISTRICT SIMALUNGUN DISTRICT - Lilis Hutagalung; Riahdo Agustian Purba; Hadi Panjaitan (International Conference on Health Science, Green Economics, Educational Review and Technology, 2019)
This study aims to determine the effect of discipline and work motivation on teacher performance at SMA swasta Bina Guna, Tanah Jawa district, Simalungun regency. The research method used is descriptive quantitative method with data analysis, namely validity test, reliability test, normality test, multiple linear regression analysis, coefficient of determination (r2), and hypothesis testing. The population in this study were all teachers of SMA Swasta Bina Guna Tanah Jawa as many as as 34 people. The data source of this research is primary data by using research instrument in the form of a questionnaire. The results of this study indicate that partially the discipline variable (X1) and work motivation variable (X2) have a significant positive effect on teacher performance at SMA Swasta Bina Guna Tanah Jawa.